2018
DOI: 10.3390/ijms19102982
|View full text |Cite
|
Sign up to set email alerts
|

Humanin Attenuates NMDA-Induced Excitotoxicity by Inhibiting ROS-dependent JNK/p38 MAPK Pathway

Abstract: Humanin (HN) is a novel 24-amino acid peptide that protects neurons against N-methyl-d-aspartate (NMDA)-induced toxicity. However, the contribution of the different mitogen-activated protein kinases (MAPKs) signals to HN neuroprotection against NMDA neurotoxicity remains unclear. The present study was therefore aimed to investigate neuroprotective mechanisms of HN. We analyzed intracellular Ca2+ levels, reactive oxygen species (ROS) production, and the MAPKs signal transduction cascade using an in vitro NMDA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…HN has been shown to protect cultured rat cortical neurons from NMDA-induced neurotoxicity, an effect that seems to be time- and concentration-dependent (Cui et al, 2014, 2017; Yang et al, 2018). In this study, we aimed at studying HN effects on structural synaptic plasticity in glutamate-induced dendritic atrophy and synapse alterations (Podestá et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HN has been shown to protect cultured rat cortical neurons from NMDA-induced neurotoxicity, an effect that seems to be time- and concentration-dependent (Cui et al, 2014, 2017; Yang et al, 2018). In this study, we aimed at studying HN effects on structural synaptic plasticity in glutamate-induced dendritic atrophy and synapse alterations (Podestá et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown in both cellular and animal models that oxidative stress upregulates the expression and activity of BACE1 through the activation of the c-Jun N-terminal kinase/activator protein1 pathway [58,59,60,61]. Kim et al reported that treating SK-N-MC cells with palmitic acid conjugated with bovine serum albumin (PA-BSA) results in an increased expression of BACE1 and Aβ production through the G protein-coupled receptor 40 (GPCR40) [62].…”
Section: Discussionmentioning
confidence: 99%
“…It has depicted that ROS-mediated oxidative stress can activate the pathway of MAPKs including ERK, JNK, and p38 in neurons (Samanta et al, 1998; Kamata et al, 2005; Yang et al, 2018). The prevention of ROS accumulation by a ROS scavenger, namely, NAC, abrogates JNK and p38 MAPK activation and subsequently promotes neuronal survival under NMDA-induced excitotoxic conditions (Yang et al, 2018), indicating the critical role of ROS-mediated JNK and p38 MAPKs activation in neuronal apoptosis. Although the mechanism for ROS-mediated activations of JNK and p38 MAPK is not well understood, it implicates that JNK and p38 serve as the potential targets for modulating neuronal apoptosis during seizures and/or epileptogenesis.…”
Section: Oxidative Stress Signaling and Neuronal Apoptosismentioning
confidence: 99%